Immediate oral surgical management of external dental fistula: Technical note of immediate tooth autotransplantation. Issue 6 (November 2021) - Ohga, Noritaka; Iori, Takashi; Sakata, Ken-ichiro; Watanabe, Haruhisa; Asaka, Takuya; Sato, Jun; Kitagawa, Yoshimasa
Abstract: Tooth autotransplantation, that is the surgical movement of a tooth from its original location to another site within the same person, is an alternative to dental implantation because it can save time, provide faster healing and function, and has esthetic advantages. A unique sensory system can be maintained, and the procedure promotes proper healing of the periodontal environment. We report on a case of external dental fistula with apical periodontitis, in which immediate tooth autotransplantation of the right mandibular posterior tooth (tooth 47) was performed with a favorable outcome 6 years postoperatively. An important advantage of this procedure is that the transplanted tooth functions early at the recipient site and this procedure is minimally invasive therapy for apical periodontitis of mandibular molars accompanied with an external dental fistula.